ChemInform Abstract: Metal‐Free Oxidative Cascade Cyclization of Isocyanides with Thiols: A New Pathway for Constructing 6‐Aryl(alkyl)thiophenanthridines. Issue 38 (September 2016) - Yang, Ziqi; Song, Xiangyang; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Duan, Haifeng; Lin, Yingjie
Abstract: The title reaction tolerates various substituents in both partners and is proposed to proceed through a free radical mechanism.